Potential Role of Amino Acids in the Adaptation of Chicks and Market-Age Broilers to Heat Stress - Chowdhury, Vishwajit S.; Han, Guofeng; Eltahan, Hatem M.; Haraguchi, Shogo; Gilbert, Elizabeth R.; Cline, Mark A.; Cockrem, John F.; Bungo, Takashi; Furuse, Mitsuhiro (Frontiers in Veterinary Science, 2021)
Increased average air temperatures and more frequent and prolonged periods of high ambient temperature (HT) associated with global warming will increasingly affect worldwide poultry production. It is thus important to understand how HT impacts poultry physiology and to identify novel approaches to facilitate improved adaptation and thereby maximize poultry growth, health and welfare. Amino acids play a role in many physiological functions, including stress responses, and their relative demand and metabolism are altered tissue-specifically during exposure to HT. For instance, HT decreases plasma citrulline (Cit) in chicks and leucine (Leu) in the embryonic brain and liver. The physiological significance of these changes in amino acids may involve protection of the body from heat stress. Thus, numerous studies have focused on evaluating the effects of dietary administration of amino acids. It was found that oral l-Cit lowered body temperature and increased thermotolerance in layer chicks. When l-Leu was injected into fertile broiler eggs to examine the cause of reduction of Leu in embryos exposed to HT, in ovo feeding of l-Leu improved thermotolerance in broiler chicks. In ovo injection of l-Leu was also found to inhibit weight loss in market-age broilers exposed to chronic HT, giving rise to the possibility of developing a novel biotechnology aimed at minimizing the economic losses to poultry producers during summer heat stress. These findings and the significance of amino acid metabolism in chicks and market-age broilers under HT are summarized and discussed in this review.